2012
DOI: 10.4085/1062-6050-47.3.02
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Burnout in Graduate Assistant Certified Athletic Trainers

Abstract: Context: Graduate assistant athletic trainers (GAATs) must balance the demands of clinical care and the academic load of graduate-level students.Objective: To examine burnout among GAATs with clinical assistantships at National Collegiate Athletic Association (NCAA) Division I institutions and to identify the personal and situational variables that are related to burnout.Design: Cross-sectional study. Setting: Division I universities offering graduate assistantship programs.Patients or Other Participants: Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 18 publications
1
38
0
2
Order By: Relevance
“…High levels of stress and long work hours put GAs at risk for burnout, especially those in the NCAA Division I setting. 66 …”
Section: Successmentioning
confidence: 99%
“…High levels of stress and long work hours put GAs at risk for burnout, especially those in the NCAA Division I setting. 66 …”
Section: Successmentioning
confidence: 99%
“…Researchers 32 have demonstrated that effective onboarding can lead to improved professional and organizational commitment, reduced stress, and improved performance. Graduate assistant ATs are susceptible to burnout as a precursor to departure from the organization 33 ; thus, an orientation session that addresses the expectations and responsibilities of the role may reduce the chance for burnout.…”
Section: Orientationmentioning
confidence: 99%
“…We used a short self-report burnout scale, initially created and validated by Mazerolle et al, 17,18 that reflected measures first used by Netemeyer et al 30 when validating an instrument to measure levels of work-family conflict and various constructs such as burnout, job satisfaction, and turnover. The questions were developed by Mazerolle et al 3 when measuring the effect of workfamily conflict on several outcome variables and before the development of a more specific athletic training burnout measurement. A short-measure scale of burnout was necessary as a means to reasonably measure the concept in our study.…”
Section: Instrumentationmentioning
confidence: 99%
“…In fact, burnout has been reported to affect athletic training students, 1,2 graduate assistant ATs, 3 ATs in the collegiate and secondary school settings, [4][5][6][7][8][9] and program directors. 10 Burnout is defined as a psychological state of mental weariness that often occurs when work stresses become too much for an individual to handle.…”
mentioning
confidence: 99%